Psychological Well-Being of Ukrainians under Martial Law: Social Implications and Educational Perspectives on Coping Strategies - Shevchenko, Antonina; et al. (European Journal of Social Science Education and Research, 2026)
The aim of the paper was to analyze the influence of martial law on stress practices and the safeguarding of mental well-being among Ukrainians. The goal of the study was to evaluate the psychological comfort of Ukrainian people during an extended period of martial law, and to detect the main anxiety management tactics. To combine a quantitative survey with qualitative expert interviews, a mixed-methods approach was used. The stress level was evaluated using the PSS-10 scale. The psychological comfort was assessed using the WHO-5 index. Descriptive statistics and content analysis of expert interviews were conducted. The standard stress level documented in the survey exceeded the threshold. The lowest scores were observed among respondents from groups of internally displaced individuals and inhabitants of territories under occupation. These results highlight the importance of applying community-based psychosocial programs.